2018
DOI: 10.1042/cs20180684
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic plaque instability in carotid arteries: miR-200c as a promising biomarker

Abstract: Early recognition of vulnerable carotid plaques could help in identifying patients at high stroke risk, who may benefit from earlier revascularisation. Nowadays, different biomarkers of plaque instability have been unravelled, among these miRNAs are promising tools for the diagnosis and treatment of atherosclerosis. Inflammation, reactive oxygen species (ROS) and endothelial dysfunction play a key role in unstable plaques genesis. We showed that miR-200c induces endothelial dysfunction, ROS production and a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 46 publications
4
36
0
Order By: Relevance
“…Further, circulating miR-200c correlates with cardiac hypertrophy and diastolic dysfunction as assessed by E/e ′ and miR-200a with cardiac hypertrophy and arterial stiffness. In light of the findings of the present work and of the previously described negative effects of miR-200c and miR-200a on endothelial [24,25,29,63] and vascular smooth muscle cells [31] and cardiac [45][46][47] function, the upregulation of these miRNAs could play a role in the inflammation and oxidative stress upregulation, increasing the risk of adverse CV events in psoriatic patients.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Further, circulating miR-200c correlates with cardiac hypertrophy and diastolic dysfunction as assessed by E/e ′ and miR-200a with cardiac hypertrophy and arterial stiffness. In light of the findings of the present work and of the previously described negative effects of miR-200c and miR-200a on endothelial [24,25,29,63] and vascular smooth muscle cells [31] and cardiac [45][46][47] function, the upregulation of these miRNAs could play a role in the inflammation and oxidative stress upregulation, increasing the risk of adverse CV events in psoriatic patients.…”
Section: Resultssupporting
confidence: 70%
“…Recently, we found that miR-200c is upregulated in carotid plaques and its expression is higher in unstable vs. stable plaque, its expression levels correlated with inflammatory markers, and circulating miR-200c levels were highly upregulated in the plasma of atherosclerotic patients compared to healthy subjects [29].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The results revealed that US and UTMD both showed the potential in upregulation of miR-200c. The levels of miR-200c in MDA231 cells of UTMD group were higher than those of control and US groups, which was similar to the findings in previous studies on the relationship of oxidative stress and miR-200c 27,28 . MiR-200c has been identified to play a central role in cancer aggressiveness by controlling tumor spreading and drug resistance through a double negative-feedback loop with the transcription factor ZEB1 [5][6][7]29 .…”
Section: Discussionsupporting
confidence: 89%